2023
DOI: 10.1146/annurev-publhealth-071521-023913
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Determinants of Digital Health Equity: A Literature Synthesis to Advance the Field

Abstract: Current digital health approaches have not engaged diverse end users or reduced health or health care inequities, despite their promise to deliver more tailored and personalized support to individuals at the right time and the right place. To achieve digital health equity, we must refocus our attention on the current state of digital health uptake and use across the policy, system, community, individual, and intervention levels. We focus here on ( a) outlining a multilevel framework underlying digital health e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 85 publications
2
40
0
Order By: Relevance
“…ACHIEVE is an integrated multicomponent intervention (mHealth app, provider dashboard, CGM, social needs referrals and team-based care), employs a SCT paradigm and is informed by prior informatics-based and behavioural-based interventions to promote glycaemic control among non-pregnant individuals with diabetes 59–61. Few existing apps for prenatal care provide comprehensive evidence-based educational content, tracking tools, UCD and the potential for integration with the EHR 62 63.…”
Section: Discussionmentioning
confidence: 99%
“…ACHIEVE is an integrated multicomponent intervention (mHealth app, provider dashboard, CGM, social needs referrals and team-based care), employs a SCT paradigm and is informed by prior informatics-based and behavioural-based interventions to promote glycaemic control among non-pregnant individuals with diabetes 59–61. Few existing apps for prenatal care provide comprehensive evidence-based educational content, tracking tools, UCD and the potential for integration with the EHR 62 63.…”
Section: Discussionmentioning
confidence: 99%
“…Third, Latinxs reported that a bilingual intervention increased accessibility to non-English speaking users. This last point highlights the importance of making evidence-based interventions available for individuals who do not speak English ( Lyles et al, 2023 ; Ramos & Chavira, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increasing patients' capacity and skills in using telehealth, platforms can be designed to be easier to use by older adults, ultimately reducing the amount of training and support needed at the outset. 114,115 Considering caregivers' perspectives, both jointly and independently of patients, can identify needs specific to caregivers. 98 Overall, these considerations highlight the importance of developing technologies alongside patients, their family caregivers, and clinicians to create tools with actionable feedback to promote the sustainability of ambulatory care management.…”
Section: Caregiversmentioning
confidence: 99%